Pandemi Covid-19 dan Inovasi Usaha Online Mahasiswa (Universitas Negeri Padang, 2021)
Jakarta, as an area that has been severely affected by the Covid-19 pandemic, has disrupted various social, educational and economic activities. Many of the families of Jakarta State University students have been affected by the economic impact of Covid-19. Students who are trying to help the family economy start and develop online businesses. Online business is very appropriate for students to live and develop, in addition to not requiring large capital, students generally master the use of technological devices, making it easier for them to market the products being sold. The implementation of PSBB in Jakarta has reduced activities outside the home, opening up opportunities for the development of online businesses developed by UNJ students. For some people, Covid-19 is an obstacle, obstacle and threat, in the business world, but Covid-19 can be used as an opportunity when we can innovate by seeing and developing strategies to adapt to the midst of the Covid-19 pandemic.